Role of family factors in adolescent delinquency in an Elazig/Turkey reformatory - Isir, Aysun Baransel; Tokdemir, Mehmet; Kucuker, Hudaverdi; Dulger, Hikmet Ergin (Wiley, 2007)
Family is one of the most important factors in the social and psychological progress of an adolescent. Social behavior disorders in childhood have been reported to be caused by many factors that may lead children to commit a crime. Our study included a total of 106 convicted adolescents from Eastern Turkey in a reformatory and 126 unconvicted adolescents with a similar socio-economic status. A survey form was completed during a face-to-face interview and a review of official records was undertaken. The role of family disruption, education levels of parents, the rate of imprisonment among first- and second-degree relatives, migration as a family from their place of birth, and the number of delinquent children in the family were evaluated. There was a significant difference between the conditions in the families of convicted and unconvicted adolescents. Family factors play an important role in the development of adolescent delinquency. To prevent or decrease this rate of childhood or adolescent delinquency, there needs to be an improvement in the socio-cultural conditions of families.
Keywords: forensic science; delinquency; adolescent; family; disruption; imprisonment; parent education